Virtual reconstruction of the San Pedro del Gallo Prison on the Camino Real de Tierra Adentro in Mexico - Carrillo, Roberto (2024)
Research on fortifications and military architecture is quite scarce, efforts to interpret and reconstruct these spaces, in the cases where physical evidence of their existence have been lost, are so as well. The purpose of this paper is precisely to show what is a presidio, as well as the spaces and activities that constituted said structure. This is achieved through a historical and a virtual reconstruction, where the latter is carried out through an architectural survey. Hopefully, it will revalue these edifices and perhaps, in the future, we will put forth a proposal that the fortifications of the Camino Real north of Tierra Adentro be declared cultural heritage, in the category of military or fortified heritage.